Draft Annual Plan 2010-2011 West Bengal - Planning Commission (Planning Commission, 2010)
The State’s achievement in rice production is satisfactory and during 2008-2009, the production of that crop was estimated at 155 lakh MT, from 58.79 lakh ha. The average productivity was 2.6 MT/ha. During 2009-2010 and 2010-2011, the targeted production of rice is 168 lakh MT and 176 lakh MT respectively. At the same time, the projected target of rice productivity is 2.87 MT /ha.
Development and Planning Department, Government of West Bengal
Government of West Bengal